Efeitos do Fármaco Antidiabético Metformina sob os parâmetros fisiológicos de Tambaqui, Colossoma Macropomum - Martins, Malba Geane Rosa (2024)
Pharmaceuticals are emerging contaminants that are not regularly monitored and are constantly being introduced into the aquatic ecosystem, and their impacts on non-target organisms are still poorly understood. As a priority, metformin (MET) is one of the most widely used hypoglycemic agents in the treatment of Type 2 Diabetes Mellitus, whose presence in aquatic environments has been detected at concerning concentrations worldwide, causing undesirable effects on aquatic biota and the local ecosystem. The aim of this study was to evaluate the potentially toxic effects of acute exposure to MET on the Amazonian teleost Colossoma macropomum, with emphasis on alterations in energy metabolism. The fish were randomly divided into four groups (n=10) control and exposed to different environmental concentrations of MET (10 μg L -1 , 80 μg L -1 , and 400 μg L -1 ) for 48 hours. Blood samples were collected for hematological analysis and plasma separation. Liver and muscle samples were collected and frozen for biochemical biomarker analysis of energy metabolism. Subsamples were fixed for histopathological analysis. After the leukocyte differential analysis, a significant increase in circulating monocytes was observed in the treated groups compared to the control group, suggesting an immune system response to MET concentrations in a dose-dependent manner. There were also adjustments in energy metabolism, evidenced by a reduction in hepatic glycogen in the group exposed to 10 μg L -1 to maintain plasma glucose and a decrease in free amino acids in plasma with a significant increase in white muscle, being the most pronounced alterations. The increase in MET concentration indicates a concentration-dependent response, suggesting that the exacerbated disposal of this drug into the environment may lead to deleterious effects on fish when exposed to high concentrations and long exposures. In acute exposure of 48 hours, no hepatotoxicity was observed in the analysis of hepatic morphology; however, there is a metabolic recruitment for detoxification and animal survival.